Penjatuhan Sanksi Pidana Dalam Putusan No. 379/PID.SUS/2021/PN PGP Terhadap Pelaku Tindak Pidana Narkotika Ditinjau Dari Asas Legalitas - Arinta, Janea; Toni (Shofanah Media Berkah, 2024)
Decision No. 379/Pid.Sus/2021/PN.PGP is the decision of the Pangkalpinang District Court which decided the Narcotics crime case. The legal facts stated that the convict had been convicted in the same case and had fulfilled the elements as intended in the regulations regarding recidivism in the Narcotics Law, but this was not implemented in the judge's considerations or in his decision. The aim of this research is to determine the imposition of criminal sanctions on perpetrators who repeat narcotics crimes and how appropriate criminal sentences are imposed on perpetrators in terms of the principle of legality. The research method used is Normative Juridical legal research, while the approach used is the case approach. The research results show that Decision number 379/Pid.Sus/2021/PN.PGP still requires better judge consideration, because the decision does not consider the element of the convict's actions as a repetition of crimes based on the Principle of Legality. The convict was sentenced to 6 (six) years and 6 months in prison, where the sentence was lighter than the previous sentence, in Decision Number 44/Pid.Sus/2016/PN PGP, namely imprisonment for 7 (seven) years. Article 144 paragraph (1) of the Narcotics Law states that a recidivist must receive a heavier sentence. However, the article regarding recidivism was not included in the judge's considerations, even though if it was adjusted to this article, the perpetrator could receive heavier sanctions, namely the maximum penalty increased by 1/3. This shows that the decision does not apply the principle of the Principle of Legality.